Germination of broccoli organic seeds treated with thermotherapy - Soriano, F.; Claudio, M. T. R. [UNESP]; Cardoso, A. I. I. [UNESP]; Nascimento, W. M.; Silva, P. P.; Rosseto, M. (Int Soc Horticultural Science, 2019)
Thermotherapy has a significant potential to control seedborn pathogens in seeds produced in organic system, but there are very few studies about this technology and not always focused on its effect on seed physiological quality. Thus, the aim of this research was to study the effect of thermotherapy on broccoli seed germination. Evaluations were carried out in the vegetable seed laboratory of the Faculty of Agricultural Sciences, located in Botucatu, Sao Paulo state, Brazil. Three seed lots (ABD, ED and SSA) of broccoli produced in organic systems were submitted to moist thermotherapy treatments at 60 and 55 degrees C for four periods: 0, 20, 40 and 60 min. Soon after treatment, seed germination was analysed in completely randomized design, with four replicates of 50 seeds each. A second germination test was performed six months after thermotherapy treatment with seeds treated at 55 degrees C only. Germination was drastically reduced in seeds treated at 60 degrees C, for all time periods of the treatment. Linear reduction in seed germination in relation to time period of treatment in the least vigorous seed lot (ED) was observed at 55 degrees C, but it did not affect germination in the other two lots in its first test, performed soon after the thermotherapy treatment; at six months after that treatment, a reduction in the three lots was noted. So, it is concluded that thermotherapy of broccoli seeds at 55 degrees C should not be performed for over 20 min, if the initial seed vigor is low. However, 60 min used for seed lots more vigorous when storage of the seeds is not necessary.
Keywords: Brassica oleracea var. italica; heat treatment; germination